Utilization of Banana Pseudostem Liquid Fertilizer and NPK Fertilizer in Enhancing the Growth and Production of Sticky Corn - Edwin Purwanto, Aldo; Ilham Mukhlisin; Trisnani Alif; Andarula Galushasti (KHD Production, 2026)
Corn production in Jember has been declining every year due to soil fertility degradation caused by the unbalanced use of synthetic chemical fertilizers. Reducing fertilizer doses and adding POC (liquid organic fertilizer) made from banana pseudostems are expected to be a solution. The aim of this research is to examine the response of corn plants to the application of banana pseudostem liquid organic fertilizer (POC) concentrations and NPK doses. This study will be conducted from July to December 2024 using a factorial randomized block design (RBD). The first factor is the NPK fertilizer dosage, which consists of: 225 kg/ha, 200 kg/ha, and 175 kg/ha. The second factor is the concentration of banana pseudostem POC with control level, 200 ml/l, 250 ml/l, and 300 ml/l. The parameters observed included plant height, number of leaves, stem diameter, cob diameter, cob length, dry weight of the cob, sweetness content, and 100-seed weight. The results of this study show an interaction, particularly in stem diameter, where the best results were found in the treatment of 175 kg/ha + control with a result of 1.96 cm. It was found that the NPK dose of 175 kg/ha produced the best results in plant height (156.12 cm), number of leaves (10.29 leaves), and cob diameter (52.7 mm).